Commercialization of agriculture and food security: Development strategy and trade policy issues - Islam, Nurul (International Food Policy Research Institute, 1994)
The choice between subsistence food crops, on the one hand, and cash crops, especially nonfood cash crops predominantly meant for exports, on the other hand, is a subject of considerable debate among policy makers as well as development specialists. The debate raises issues not only at the level of farming households but also at the level of national and international policies, including macroeconomic policies such as trade and exchange rate policies. This chapter reviews and focuses on those aspects of principal relevance in the context of an overall agrcultural development strategy and food security.